Theses developed, time of completion and publication as scientific papers in a university faculty of veterinary medicine and zootechnics of Peru - Gómez-Quispe, Oscar (2022)
The time required to execute and defend undergraduate theses and the relationship between the number of theses supported with the scientific articles derived from theses that were published in indexed journals were analyzed. The study was carried out with theses work carried out at the Faculty of Veterinary Medicine and Zootechnics of the Universidad Nacional Micaela Bastidas de Apurímac in the period 2012-2018. The information available in the faculty and in the institutional repository of the university was collected. The publications indicated by the thesis advisers with the CTI-Vitae registry of the National Council of Science, Technology and Technological Innovation (CONCYTEC) and the publications available in international scientific databases were verified. Likewise, the date of approval of the thesis project and the date of defense of the thesis, the number of theses supported by advisor, and the number of published papers in scientific journals derived from thesis were recorded. In general, 59.5% of the defended theses required an execution time of less than or equal to 18 months and 20.3% took 24 months or more to be concluded. There was no relationship between the number of undergraduate theses by advisor and publications as papers in scientific journals indexed in Scopus or Web of Science (r=0.381, p=0.178).